Qualidade fisiológica de sementes de soja submetidas à ar resfriado e mantidas em diferentes condições de armazenamento - Silva, Emanueli Pereira da (2021)
In order to meet the logistic demand for the production and commercialization of soybean seeds (Glycine max (L.) Merril) the storage technique is very important in helping to maintain the quality of seed lots, and consequently the success of the crop establishment. For this, some techniques such as storage in controlled environments or dynamic seed cooling at the bagging time are being used. The objective of the work was to evaluate whether the application of cold in soybean seeds, maintains its physiological quality for a longer time under different storage conditions. The experiment was carried out in the seed beneficiation unit and in the Seed Analysis Laboratory of the agricultural cooperative Tradição, in Pato Branco, Paraná, and in the Didactic Laboratory of Seed Analysis at UTFPR, Campus Dois Vizinhos; two seed lots were tested, different in seed size (5.5 and 6.5 mm). Samples were collected at four times (0, 2, 4 and 6 months), and then submitted to: first count, germination, accelerated aging, mechanical damage, seedling emergence test, weight of dry mass and weight of 1,000 seeds. The experimental design was completely randomized in a 2x2x4 trifactorial scheme (dynamic cooling: with and without; storage location: cold chamber and conventional warehouse; four evaluation periods). After compilation, the dataset was tabulated and submitted to the Lilliefors test to verify the homogeneity of the variance. Fulfilling the assumptions, the analysis of variance was performed to verify the level of significance (P < 0.05) of the isolated factors and also the interaction between the factors. In case of significance between the qualitative factors, the data were subjected to the Skott-Knott test at the level of 5% probability of error, and for the quantitative factors, polynomial regression analysis. It was concluded that the dynamic artificial cooling followed by maintenance in a cold and dry chamber (10 ° C and 20% RH), guaranteed the preservation of the physiological quality of soybean seeds for up to 180 days. Soybean seeds subjected to dynamic cooling during bagging, present superior physiological quality during storage, when compared to uncooled seeds. Soybean seeds stored in a cold and dry chamber (10 ° C and 20% RH) show superior physiological quality during storage, when compared to seeds stored in an environment without temperature control.